Targeting IL-21 to tumor-reactive T cells enhances memory T cell responses and anti-PD-1 antibody therapy - Ying Li (Nature Portfolio, 2021)
The lack of an efficient anti-tumor T cell response contributes to the failure of anti-PD1 therapy. Here, the authors show a potential strategy to improve the therapeutic effects of anti-PD-1 antibody by simultaneously targeting IL-21 to tumor-reactive T cells in vivo.